2022
DOI: 10.1161/jaha.121.023314
|View full text |Cite
|
Sign up to set email alerts
|

Associations of High‐Sensitivity Troponin and Natriuretic Peptide Levels With Serious Adverse Events in SPRINT

Abstract: Background Assessing the risk of serious adverse events (SAEs) during hypertension treatment is important for understanding the benefit‐harm trade‐offs of lower blood pressure goals. It is unknown whether high‐sensitivity cardiac troponin T (hs‐cTnT) and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) provide information about SAEs. Methods and Results In SPRINT (Systolic Blood Pressure Intervention Trial), hs‐cTnT and NT‐proBNP wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…[9,10] However, with the introduction of highly sensitive troponin kits, studies conducted in recent years have found a relationship between high-sensitivity troponin and syncope in terms of detecting poor outcomes in the patient group. [11–14] In our study, the cutoff value for hs-cTnT determination was determined as 7.3. Compared to previous studies, a higher diagnostic value of troponin was observed.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] However, with the introduction of highly sensitive troponin kits, studies conducted in recent years have found a relationship between high-sensitivity troponin and syncope in terms of detecting poor outcomes in the patient group. [11–14] In our study, the cutoff value for hs-cTnT determination was determined as 7.3. Compared to previous studies, a higher diagnostic value of troponin was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies examined this relationship in the non-diabetic population. In the post hoc analysis of the Systolic Blood Pressure Intervention Trial (SPRINT), a US trial comparing blood pressure targets in 9361 persons without diabetes, elevated baseline level of Hs-cTnT was found positively associated with all-cause mortality, heart failure, and composite adverse severe events [ 20 , 21 ]. However, analyzing data from The Women’s Health Study, Everett et al found that in women without diabetes, elevated Hs-cTnT was not significantly associated with cardiovascular death, myocardial infarction, stroke, and their combination [ 22 ].…”
Section: Discussionmentioning
confidence: 99%